2012
DOI: 10.1111/j.1349-7006.2011.02191.x
|View full text |Cite
|
Sign up to set email alerts
|

The heat shock protein 90 inhibitor, AT13387, displays a long duration of action in vitro and in vivo in non‐small cell lung cancer

Abstract: A ubiquitously expressed chaperone, heat shock protein 90 (HSP90) is of considerable interest as an oncology target because tumor cells and oncogenic proteins are acutely dependent on its activity. AT13387 (2,4-dihydroxy-5-isopropyl-phenyl)-[5-(4-methyl-piperazin-1-ylmethyl)-1,3-dihydro-isoindol-2-yl] methanone, L-lactic acid salt) a novel, high-affinity HSP90 inhibitor, which is currently being clinically tested, has shown activity against a wide array of tumor cell lines, including lung cancer cell lines. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
72
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 47 publications
1
72
1
Order By: Relevance
“…First-generation geldanamycins and second-generation non-geldanamycin agents, including AT13387, as well as AUY922 and ganetespib, demonstrate preferential accumulation in tumors, with long intratumoral t 1/2 (often detectable for 7-10 days in tumor), justifying once-weekly regimens (11)(12)(13)(14). Here, AT13387 has demonstrated preliminary activity against KIT-driven GIST, including a partial response in a patient with tumor harboring mutations conferring resistance to TKIs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…First-generation geldanamycins and second-generation non-geldanamycin agents, including AT13387, as well as AUY922 and ganetespib, demonstrate preferential accumulation in tumors, with long intratumoral t 1/2 (often detectable for 7-10 days in tumor), justifying once-weekly regimens (11)(12)(13)(14). Here, AT13387 has demonstrated preliminary activity against KIT-driven GIST, including a partial response in a patient with tumor harboring mutations conferring resistance to TKIs.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the long intratumoral t 1/2 noted with these agents, the suppression of client protein expression has been noted to be more transient. For example, in mutant EGFR (L858R/T790M) NCI-H1975 NSCLC xenografts, depletion of mutant EGFR has been documented to last a duration of 72 hours or shorter in response to a single dose of AT13387 or ganetespib (13,14). In a clinical evaluation of once-weekly ganetespib in GIST (29), tumor biopsies demonstrated only transient depletion of KIT and inhibition of downstream signaling pathways, suggesting that the once-weekly regimen was suboptimal for producing prolonged client protein depletion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AT13387, a nonansamycin HSP90 inhibitor provided by Astex Pharmaceuticals, was reported to suppress cell growth of various cancer types (non-small-cell lung carcinoma, and nasopharyngeal carcinoma) by previous reports (28,29). No previous study reported, the effectiveness of AT13387 for cholangiocarcinoma cell lines; however, Shapiro and colleagues reported a phase I study of AT13387 for solid tumors, including one cholangiocarcinoma patient.…”
Section: Discussionmentioning
confidence: 89%